2015
DOI: 10.1002/2015jb011900
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer bonding energy of layered minerals: Implication for the relationship with friction coefficient

Abstract: The frictional strength of layered minerals is an important component of fault slip physics. A low‐friction coefficient of these minerals has been attributed to the interlayer bonding energy (ILBE) of their weak interlayer bonding. The ILBE used for discussing the friction coefficient is based on a simple electrostatic calculation; however, the values should be revisited by precise calculations based on quantum mechanics. In this study, the ILBEs of layered minerals were calculated by using the density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Morrow et al . [], Moore and Lockner [], and Behnsen and Faulkner [] found that the dry frictional strength of the 2:1 sheet silicate minerals is correlated with the strength of their calculated interlayer, (001), bonds [ Giese ; Sakuma and Suehara ]. The (001) bond strength is a function of the layer charge and whether or not the mineral is dioctahedral or trioctahedral [ Giese ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morrow et al . [], Moore and Lockner [], and Behnsen and Faulkner [] found that the dry frictional strength of the 2:1 sheet silicate minerals is correlated with the strength of their calculated interlayer, (001), bonds [ Giese ; Sakuma and Suehara ]. The (001) bond strength is a function of the layer charge and whether or not the mineral is dioctahedral or trioctahedral [ Giese ].…”
Section: Discussionmentioning
confidence: 99%
“…Frictional strength of montmorillonite and its dependence on normal stress are strongly dependent on whether the sample is dry or wet and, if wet, are functions of saturation state. Morrow et al [2000], , and Behnsen and Faulkner [2012] found that the dry frictional strength of the 2:1 sheet silicate minerals is correlated with the strength of their calculated interlayer, (001), bonds [Giese 1978;Sakuma and Suehara 2015]. The (001) bond strength is a function of the layer charge and whether or not the mineral is dioctahedral or trioctahedral [Giese 1978].…”
Section: Friction Mechanisms Of Wet Versus Dry Montmorillonitementioning
confidence: 99%
“…Moore and Lockner (2004) suggested that the (001) bonding strength is a primary factor controlling frictional coefficient of the sheet silicates; however, recent experiments by Behnsen and Faulkner (2012) found the friction coefficient of various clay minerals were deviated significantly from the value predicted from the electrostatic separation energy. Sakuma and Suehara (2015) calculated interlayer bonding energy using the first-principles based density functional theory without using the empirical approximation of charge distributions in minerals, and they showed that there is no clear correlation with the frictional strength for layered minerals. Experiments using a single crystal of muscovite showed a markedly lower shear resistance than those using powder sample, suggested that the sliding does not necessarily occur only on the basal plane in the clay-bearing gouges (Kawai et al 2015).…”
Section: Effect Of Humidity and Interlayer Cations On The Frictional mentioning
confidence: 99%
“…Especially, surfaces and interlayers of phyllosilicate were studied by DFT calculations [13][14][15]. The quantum chemical calculations can identify the most steady state by comparing the total energies of different structures, and analyzing the interaction between V and oxygen in the lattice, which further affects the related physical and chemical properties of muscovite.…”
Section: Structure and Modelsmentioning
confidence: 99%